Effect of Plasma and Fiber Position on Flexural Properties of a Polyethylene Fiber-Reinforced Composite - Spyrides,Silvana M. M. (2015)
Abstract: The aim of this study was to evaluate the effect of plasma treatment using argon and oxygen gases, combined with fiber position on flexural properties of a fiber-reinforced composite. Eleven groups were evaluated, a non-reinforced control group and 10 groups reinforced with InFibra, a woven polyethylene fiber, varying according to the plasma treatment and fiber position. The samples were prepared using a stainless steel two-piece matrix. The three point bending test was performed in an EMIC testing machine. Flexural strength (FS) and flexural deflection (FD) were calculated from initial (IF) and final (FF) failure. Data were evaluated statistically using Kruskal-Wallis and Mann-Whitney tests (p<0.05). For IF, in all groups with fibers placed on the base, the FS and FD values were significantly higher than those positioned away from the base. The highest value of FS was obtained in the group treated with O 3 min (296.2 MPa) and the highest value of FD was obtained in the group treated with 1 min (0.109 mm). For FF the FS and FD values obtained for the groups with fibers positioned away from the base were similar or higher than those placed on the base. The highest FS value was obtained in the group treated with 1 min (317.5 MPa) and the highest FD value was obtained in the group treated with O 3 min (0.177 mm). Plasma treatment influenced FS and FD. Fiber position and plasma treatment affected the flexural properties of a fiber-reinforced composite.